(untitled) (University Heart Journal, 2023)
Background & Objectives: Coronary artery disease (CAD) accounts for the major risk factor of mortality in diabetes. Coronary angiography is the “gold-standard” technique for diagnosing and evaluating CAD. Material and Methods: The present study was undertaken at Border Guard hospital, Dhaka between the periods of November - 2017 to December 2021. Percutaneous coronary angiography (CAG) was performed in 204 consecutive patients with suggestive of ischaemic chest pain. The population consisted of 88 cases which are diabetic and 116 cases nondiabetic Results: We observed angiographic lesion among both groups comparing site & number of vessel(s) involvement and also average percentage of stenosis. The presence of coronary risk factors was not significantly different between the two populations. Total positive angiographic lesion was (61.5%) in both groups. Among the Diabetes mellitus patients positive CAG finding (69.3%). The recognized lesions were single vessel disease (SVD) 23 (26.1%), double vessel disease (DVD) 14 (15.9%), triple vessel disease (TVD) 24 (27.3%) percentage of vessel stenosis 82.63%. On the other hand, total positive angiographic lesion was 70 (53.4%) in non-diabetic group; among them single vessel disease (SVD) 30 (25.9%), double vessel disease (DVD) 15(12.9%), triple vessel disease (TVD) 17 (14.7%). No diffuse lesions was found and average vessel stenosis was 78.03%. The results of the angiographic finding suggest that diabetic patients have a higher incidence of coronary heart disease (CHD), DVD, TVD, diffuse lesion & marked stenosis of coronary vessel than non-diabetic patient. Conclusion: CAD in diabetics had considerably higher percent of severe and unpredictable presentation. This increased frequency of complex lesion morphology is more difficult to treat by definitive intervention like percutaneous transluminal coronary angioplasty (PCI) & coronary artery bypass graft (CABG). Diabetics have a higher risk factor profile and poor clinical outcome. Early diagnosis and appropriate management will reduce the risk of complication after the onset of disease. University Heart Journal 2023; 19(1): 5-9